Peyronie's Disease: Evolving Surgical Management and the Role of Phosphodiesterase 5 Inhibitors. (2009) - Al-Shaiji, Tariq F.; Brock, Gerald B.
Abstract : Peyronie's disease (PD) is a fibrotic disorder of the tunica albuginea of the penis. It is characterized by different degrees of penile curvature and sexual dysfunction. Several medical treatments have been employed to manage the disorder, with variable success rates. Surgical therapy is reserved for patients with severe penile deformity that fails to improve with medical treatment and impedes coital function. The advantages and disadvantages of various surgical approaches have long been debated. Herein, we describe the evolving surgical techniques for PD using knowledge obtained from the contemporary literature. In addition, we discuss the emerging data regarding the role of phosphodiesterase 5 inhibitors in the management of PD.